Influence of ammonium bromide and picloram in Syngonium micropropagation - RAJANBABU, VENUGOPAL; POOMARUTHAI, MASILAMANI; SUBRAMANIAN, RAJESH; PARAMASIVAM, SIVAKUMAR; SILAMBIAH, SHRIRANGASAMI (The Indian Journal of Agricultural Sciences, 2025)
Micropropagation is a promising way to overcome difficulties in plant propagation such as time consumption, maintenance of plant uniformity and disease infection. The increased demand for the ornamental plant, Syngonium can be aptly met by the large scale multiplication through tissue cultures. The present study was carried out during rainy (kharif) season 2020 to winter (rabi) season 2023 at Anbil Dharmalingam Agricultural College and Research Institute, Tiruchirapalli, Tamil Nadu reports optimized protocol for the micropropagation of Syngonium through direct organogenesis and somatic embryogenesis pathways in two important species, Syngonium podophyllum and Syngonium auritum, respectively. Randomized block design (RBD) and single-factor ANOVA was used to analyze the effects of organogenesis and embryogenesis Direct organogenesis was achieved through the formation of axillary buds in Syngonium podophyllum using shoot tip and nodal explants in modified Murashige and Skoog (MS) media with 1 mg/L BAP and 0.1 mg/L NaH2PO4. In addition, the presence of 0.1 mg/L ammonium bromide consistently enhanced the proliferation rate up to five subculture cycles of shoot proliferation. Plant regeneration through somatic embryogenesis was achieved in Syngonium auritum using MS medium supplemented with 10 mg/L picloram and 1 mg/L 2,4-D. Embryogenic calli formed in the stem explant was devoid of nodes in Syngonium auritum and could be regenerated into full plants when subcultured in modified MS medium with 2 mg/L NAA and 1 mg/L IAA. The in vitro rooted plantlets were successfully acclimatized in portray containing 1:1 ratio vermicompost and coir pith compost soil medium and later transferred to the larger pots containing a mixture of red earth and vermicompost in 3:1 ratio. Secondary hardening was done by transferring plants to polythene bags and maintained under shade net house for six weeks until it is ready for planting in indoor or outdoor conditions.